Association of systemic lupus erythematosus and hypermobility. Issue 11 (1st November 2002) - Gumà, M; Olivé, A; Roca, J; Forcada, J; Duró, J C; Holgado, S; Casado, E; Mezquiriz, X; Tena, X
Abstract : Objective: To investigate joint laxity in patients with systemic lupus erythematosus (SLE). Setting: University Hospital. Methods: 81 patients with SLE (1999 American College of Rheumatology criteria; 72 (89%) women and nine (11%) men, mean age 42.9 (SD 16.1) years), who regularly attended a specialist SLE clinic were examined. The control group comprised 280 patients attending a general practitioner (193 (69%) women and 87 (31%) men, mean age 44.7 (SD 11.2) years). Joint laxity was measured according to the criteria of Beighton et al (total score 4 or more). A regression analysis was performed. Results: Thirty nine (48%) patients with SLE and 42 (15%) of the control group were hypermobile. A logistic regression model was developed. The odds ratio of the association between laxity and SLE after adjustment for age and sex was 2.31 in the group younger than 49 years, and 17.99 in the group aged 49 years or older. Neither the clinical and analytical profile nor the use of corticosteroids was related to joint laxity. Conclusion: Patients with SLE showed more hypermobility than controls. Hypermobility was more profound in older patients with SLE (≥49 years). Joint laxity was not associated with any clinical or analytical pattern. Treatment with corticosteroids was not related to joint laxity.